Pengaruh Budaya Organisasi dan Etos Kerja terhadap Produktivitas Kerja Melalui Motivasi Kerja Sebagai Varibel Intervening pada PT Makin Group Tbk Tebo - Ridwan, Mu’ammar; Suryani, Arna; Sudirman, Sudirman (J-MAS (Jurnal Manajemen dan Sains), 2024)
This study aims to analyze the description of organizational culture, work ethic, work motivation and employee work productivity at PT. Makin Group and analyze the influence of organizational culture and work ethic on employee work productivity through work motivation as an intervening variable at PT. Makin Group. This type of research uses descriptive verification research. The objects of this research are organizational culture, work ethic, work motivation and employee work productivity. This research uses the PLS analysis method. Based on data processing, Organizational Culture is in the high category. Then the work ethic shows a fairly high category. Furthermore, work motivation shows in the High category. Meanwhile, work productivity shows a fairly high category. Based on the research results, organizational culture does not have a significant effect on employee work motivation. Work ethic has a significant and positive effect on employee work motivation. Organizational culture does not have a significant and negative effect on employee work productivity. Work ethic has a positive and significant effect on employee work productivity. Work motivation has a positive and significant effect on work productivity. Organizational culture has no significant effect on work productivity with work motivation as an employee intervening variable and work ethic has a significant and positive effect on work productivity with work motivation as an employee intervening variable.